A radial basis function network (RBFN) for function approximation - Lucks, M. B.; Oki, N.; RamirezAngulo, J. (IEEE, 1999)
A radial basis function network (RBFN) circuit for function approximation is presented. Simulation and experimental results show that the network has good approximation capabilities. The RBFN was a squared hyperbolic secant with three adjustable parameters amplitude, width and center. To test the network a sinusoidal and sine function,vas approximated.
Keywords: Approximation theory; Bipolar transistors; Computer simulation; Electric network analysis; Function evaluation; Neural networks; Simulated annealing; Function approximation; Radial basis function network; Sinc function; Sinusoidal function; Integrated circuit testing